Long-term impact of conservation agriculture and diversified maize rotations on carbon pools and stocks, mineral nitrogen fractions and nitrous oxide fluxes in inceptisol of India - Parihar, C.M.; Parihar, M.D.; Sapkota, Tek B.; Nanwal, R.K.; Singh, A.K.; Jat, S.L.; Nayak, H.S.; Mahala, D.M.; Singh, L.K.; Kakraliya, S.K.; Stirling, Clare M.; Jat, M.L. (The Science of the total environment, 2018)
Given the increasing scarcity of production resources such as water, energy and labour coupled with growing climatic risks, maize-based production systems could be potential alternatives to intensive rice-wheat (RW) rotation in western Indo-Gangetic Plains (IGP). Conservation agriculture (CA) in maize systems has been widely promoted for minimizing soil degradation and ensuring sustainability under emerging climate change scenario. Such practices are also believed to provide mitigation co–benefits through reduced GHG emission and increased soil carbon sequestration. However, the combined effects of diversified crop rotations and CA-based management on GHG mitigation potential and other co-benefits are generally over looked and hence warrant greater attention. A field trial was conducted for 5–years to assess the changes in soil organic carbon fractions, mineral–N, N2O emission and global warming potential (GWP) of maize-based production systems under different tillage & crop establishment methods. Four diversified cropping systems i.e. maize–wheat–mungbean (MWMb), maize–chickpea–Sesbania (MCS), maize–mustard–mungbean (MMuMb) and maize–maize–Sesbania (MMS) were factorially combined with three tillage & crop establishment methods i.e. zero tilled permanent beds (PB), zero–tillage flat (ZT) and conventional tillage (CT) in a split–plot design. After 5–years of continued experimentation, we recorded that across the soil depths, SOC content, its pools and mineral-N fractions were greatly affected by tillage & crop establishment methods and cropping systems. ZT and PB increased SOC stock (0–30 cm depth) by 7.22–7.23 Mg C ha−1 whereas CT system increased it only by 0.88 Mg C ha−1as compared to initial value. Several researchers reported that SOC & mineral–N fraction contents in the top 30 cm soil depth are correlated with N2O–N emission. In our study, global warming potential (GWP) under CT system was higher by 18.1 and 17.4%, compared to CA-based ZT and PB, respectively. Among various maize systems, GWP of MMS were higher by 11.2, 6.7 and 6.6%, compared that of MWMb (1212 kg CO2–eq. ha−1), MCS (1274 kg CO2–eq. ha−1) and MMuMb (1275 kg CO2–eq. ha−1), respectively. The results of our study suggest that CA and diversified crop rotations should be promoted in north-western IGP and other similar agro-ecologies across the globe for ensuring food security, restoration of soil health and climate change mitigation, the key sustainable development goals (SDGs). [Display omitted] •Soil C fractions and N dynamics and N2O emissions from different tillage and diversified cropping systems were analysed.•The mass equivalent SOC stock and mineral-N fractions increased dramatically in CA practices.•Greater N2O fluxes occurred in CT than CA based systems.•The higher SOC and mineral-N, with lower N2O fluxes were found in MWMb and MCS than in MMS cropping system.